PENDEKATAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) UNTUK MENINGKATKAN KUALITAS PELAYANAN HYPERMARKET PADA HYPERMARKET XYZ - Matius J Situmorang; Rosnani Ginting; Aulia Ishak (Departemen Teknik Industri Universitas Sumatera Utara, 2013)
Competition in the retail companies compete for customers in a very high market where consumers will choose to shop at a retail company that has a good quality of service thus each company will compete to provide the best service to customers. Hypermarket XYZ is one that constantly seeks to improve the quality of service, however, there is less of the services provided by XYZ hypermarket which resulted in a decrease in the number of customers ranges from 2012 to 2013. Thus, hypermarket XYZ will improve service quality by understanding the needs and desires of customers and make a strategy to translate into improved technical characteristics. Appropriate method to satisfy it is the method of Quality Function Deployment (QFD). Initial stages is to see the gap between the performance of the service provided to the consumer desires. Questionnaires were distributed to 97 respondents, obtained 15 attributes into consumer desires and GAP obtained from the calculation of the greatest value -1.444. From the data processing obtained 10 technical characteristics that interior building, training (training), understanding the customer, routine monitoring, warranty administration, clarity of information, ease of access, ATM corner, employee capabilities, and inventory control with the level of interest of the greatest business value contained in training with a value of 211 and a relative cost of 8.55.